286 The influence of age and winter environment on Rumax Bovibox and Bovibox HM supplement intake behavior of winter grazing beef cattle on mixed-grass rangelands. (30th November 2020) - Wyffels, Samuel; Parsons, Cory T; Dafoe, Julia M; Boss, Darrin L; McClain, Tyrell; Carter, Boone; DelCurto, Timothy
Abstract: This study evaluated the influence of cow age and temperature adjusted for windchill (Twindchill ) on supplement intake behavior of cattle winter grazing northern mixed-grass prairie rangelands. A commercial herd of 291 (yr-1) and 316 (yr-2) bred cows were winter grazed on a 329-ha rangeland pasture for 2 years. Cows were assigned to one of six age classifications and were provided free-choice access to Rumax Bovibox HM (2018–2019) and Rumax Bovibox (2019–2020) protein blocks. The target daily intake range was 0.45–0.91 kg∙cow -1 ∙d -1 . Supplement was provided in a SmartFeedPro self-feeder system to measure individual animal supplement intake and behavior. Average daily supplement intake (expressed as kg∙cow -1 ∙d -1 ) and variation in supplement intake displayed Twindchill × cow age × yr interactions (P ≤ 0.05). There was no effect of age on daily supplement intake at below average and above average Twindchill in yr 1 (P ≥ 0.07). Age displayed a quadratic effect on daily supplement intake at average Twindchill in yr-1 (P < 0.01) but was limited to 3- and 4-yr-old cattle consuming more supplement per day than yearlings (P ≤ 0.02). During yr-2, cow age had a quadratic effect on supplement intake for all Twindchill conditions (P < 0.01) where 3-yr-old cattle consumed more supplement per day than yearlings, 5–7- and ≥ 8-yr-olds (P ≤ 0.01). Cow age exhibited quadratic effects on variation in supplement intake across all Twindchill conditions during both years (P < 0.01). However, the quadratic effects of age in yr-1 were limited to yearlings having higher variation in supplement intake than all other ages (P < 0.01). In summary, both cow age and the winter environmental conditions interacted to influence animal supplement intake behavior and, as a result, nutrient delivery efficacy in winter grazing beef cattle.